Green Marketing of Aqua Mineral Water: How Does Trust Mediate Among Generation Z? - Genoveva, Genoveva; Darmawan, Made Ramadita Wira (Indonesian Journal of Sustainability Accounting and Management, 2023)
Indonesia is the second-largest country globally that produces a very high amount of plastic waste, reaching 68 million tons. Meanwhile, plastic materials are difficult to decompose and take hundreds of years to disappear completely. This led to the increasing awareness of consumers around the world to decrease the use of plastic by choosing sustainable products. The purpose of this study is to analyze green marketing of the Aqua product and its impact among Generation Z. The variables of this research such as green product, green branding, and green advertising are independent variables, purchase decision is a dependent variable, and consumer trust is an intervening variable. This research is quantitative research using non-probability sampling with purposive sampling to spread the questionnaires with 30 questions and processed with SmartPLS 3.3.5 (Partial Least Square-Structural Equation Model). The total respondents of this research are 299 respondents with aged around 17–25 years old (generation Z) in Indonesia. The result shows that 7 hypotheses are accepted. Hence, this study explains that the green product, green branding, and green advertising will increase consumer trust and ultimately increase customer purchase decision of Aqua green products.